Ostensive signals support learning from novel attention cues during infancy - Wu, Rachel; Tummeltshammer, Kristen S.; Gliga, Teodora; Kirkham, Natasha Z. (Frontiers in Psychology, 2014)
Social attention cues (e.g., head turning, gaze direction) highlight which events young infants should attend to in a busy environment and, recently, have been shown to shape infants’ likelihood of learning about objects and events. Although studies have documented which social cues guide attention and learning during early infancy, few have investigated how infants learn to learn from attention cues. Ostensive signals, such as a face addressing the infant, often precede social attention cues. Therefore, it is possible that infants can use ostensive signals to learn from other novel attention cues. In this training study, 8-month-olds were cued to the location of an event by a novel non-social attention cue (i.e., flashing square) that was preceded by an ostensive signal (i.e., a face addressing the infant). At test, infants predicted the appearance of specific multimodal events cued by the flashing squares, which were previously shown to guide attention to but not inform specific predictions about the multimodal events (Wu & Kirkham, 2010). Importantly, during the generalization phase, the attention cue continued to guide learning of these events in the absence of the ostensive signal. Subsequent experiments showed that learning was less successful when the ostensive signal was absent even if an interesting but non-ostensive social stimulus preceded the same cued events.